2015
DOI: 10.1016/j.gmit.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach of tubo-ovarian abscesses from theory to our minimally invasive practice

Abstract: Keywords: minimally invasive treatment surgical approach tubo-ovarian abscess a b s t r a c t Background: Tubo-ovarian abscesses are entities of infectious etiology, mostly as a result of pelvic inflammatory disease. Over the past decades we verified that the treatment is lifesaving and the approach can be, and should be, minimally invasive. The advent of antibiotics, its parenteral combined administration, and the appearance of techniques of drainage, made possible a better treatment of this pathological cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Imaging-guided drainage of abscesses paired with antibiotics offers an alternative approach. Minimally invasive procedures for TO abscesses performed by the laparoscopy approach and transvaginal ultrasound-guided drainage are associated with less morbidity and a shorter hospital stay [ 10 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging-guided drainage of abscesses paired with antibiotics offers an alternative approach. Minimally invasive procedures for TO abscesses performed by the laparoscopy approach and transvaginal ultrasound-guided drainage are associated with less morbidity and a shorter hospital stay [ 10 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is usually a consequence of PID. [ 1 2 3 ] A TOA may form as an untoward consequence of a hysteroscopic procedure. This adverse outcome is rare, with an incidence rate of about only 0.2%.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence supporting early intervention within the first 24–48 h of hospital admission in those who are unlikely to respond to antibiotics 4 . Patients undergoing early surgery or radiological drainage demonstrate a faster recovery, 10 a more rapid resolution of fever, 11,12 a shorter hospital stay, 11–13 and radiological resolution rates at 6 months 14 . Rosen et al 15 have also shown that pregnancy rates were also improved in those who underwent immediate laparoscopic drainage (32%–63%) compared with those medically managed (4%–15%).…”
Section: Discussionmentioning
confidence: 99%